Upaya Perbaikan Aktivitas Dan Hasil Belajar Menggunakan Model PBL, Open-Ended Learning, Dan Pair Checks - Rosendi Aditya Suryatama Harahap; Darmiyati (CV. ITTC INDONESIA, 2023)
The problem that occurs is the low activity and learning outcomes in mathematics content. This study aims to describe the activities of educators, analyze activities and learning outcomes. The approach used was a qualitative approach with the type of PTK carried out in three meetings and the subjects studied were fourth grade students at SDN Kelayan Selatan 2 Banjarmasin. The type of data in this discovery is qualitative data obtained from observations of teacher and student activities in the learning process, as well as quantitative data in the form of learning outcomes obtained through written tests. The results showed in this study that the teacher's activities in the first meeting were in the